PENINGKATAN BUDAYA MEMBACA BERBASIS DIGITAL LIBRARY BAGI MASYARAKAT PESISIR PANTAI PEKON PUTIH DOH - Fungky Marian (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
The obstacles that occur in the Pekon Putih Doh community regarding reading interest are still low. Of course this will have an impact on the lack of knowledge and the extinction of local culture. Therefore, the local government of Tanggamus district made a program to increase interest in reading and get to know the local culture which is almost extinct so that children and adolescents in the Pekon can enjoy reading and preserve local culture and introduce it to the national and international levels. The efforts made by a team from the University of Muhammadiyah Lampung (UML) include: Initial Surveys, Counseling, Training and Demonstrations, Providing Technology Packages, and Evaluation. Based on the evaluation of the dedication that has been done, it is known that the extension and training of the digital library can increase the reading interest of the Coastal Coastal community.